Propuesta de un programa de prevención de riesgos laborales en el Taller Industrial Artola S.A. - Gamboa-Zamora, Angélica (Instituto Tecnológico de Costa Rica, 2017)
The project was carried out at Taller Industrial Artola S.A., where the main objective is to propose a risk prevention program for the workplace environment specific for the workshop, through a hazard identification, risk evaluation, determination of the administration carried out in terms of laboral safety, together with the design of controls that it will help to prevent occupational risks in the place. After applying check lists that were implemented, we have been able to identify the risks of the premises. The risk evaluation consisted in measuring the levels of noise, lighting and ergonomic conditions along with the creation of a risk matrix in accordance with the INTE 31-06-07:2011. Additionally, we conducted a study to review the company’s administration in terms of work safety through documentary review, surveys for managers and questionnaires for workers. The results of the study helped in highlighting the presence of risks at a mechanical, physical and biomechanical level due to inadequate postures, lack of space organization and the cleanliness conditions. The levels of exposure to noise in the CNC and welding areas are above 80dB(A), the lighting conditions in the workshop are not homogeneous and the levels of ergonomic risks were found medium and low (according to REBA method). This program´s proposal is an instrument that will decrease the levels of the risks in the workplace´s activities through the application of the following controls: work walkthrough/guideline for risk free procedures within work activities, guidelines for organization of space and cleanliness of the work area in accordance to 5S, tools for workplace analysis, reports for risks and situations where an incident might have occurred, training plan and the program follow up process.
Proyecto de Graduación (Bachillerato en Ingeniería en Seguridad Laboral e Higiene Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Seguridad Laboral e Higiene Ambiental, 2017.
Keywords: Prevención; Factores de riesgo; Seguridad ocupacional; Mecánica de precisión; Industria metalmecánica